Environmental conditions can have a profound effect on the trajectory of disease in the maflg(ft)/maflg(ft) model of skin barrier deficiency and atopic dermatitis - Fahy, Caoimhe Máire Róis (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2012)
The prevalence of atopic disease has increased in recent decades. The hygiene hypothesis postulates that cleaner environments contribute to this observed increase in atopy. The cutaneous manifestations of atopic dermatitis (AD) are thought to be the beginning of the atopic march. Approximately one third of patients with AD go on to develop allergic rhinitis and half will develop asthma. It is recognised that epidermal barrier dysfunction is a causal factor in the pathogenesis of AD. Loss-of-function mutations in the gene for the epidermal protein, filaggrin, convey the strongest genetic risk for AD. It has been shown that the flaky tail (maflg ft/maflg ft) mouse is a model of skin barrier deficiency.
Keywords: Dermatology, Ph.D.; Ph.D. Trinity College Dublin